Quasiclassical approximation for ultralocal scalar fields - Francisco, G. (IOP Publishing, 1986)
The author shows how to obtain the quasiclassical evolution of a class of field theories called ultralocal fields. Coherent states that follow the 'classical' orbit as defined by Klauder's weak correspondence principle and restricted action principles are explicitly shown to approximate to the quantum evolution as h(cross) to O.